Efficacy of commercial nasal bridle use in reducing feeding tube dislodgements in pediatric patients following double stage laryngotracheoplasty. (May 2020) - Mayes, Theresa; Brumbaugh, Cheryl; Vitolo, Sarah; Buchert, Melissa; Tabangin, Meredith; Myer, Charles
Abstract: Introduction: Maintaining placement of the nasogastric feeding tube (NGT) is imperative in the double stage laryngotracheoplasty (dsLTP) patient because of concerns for adequate nutrition and hydration in the postoperative period. Additionally, multiple reinsertions due to displacement potentiate surgical morbidities. The purpose of this study was to compare NGT dislodgment rates in children with and without a commercial nasal bridle following a dsLTP surgical procedure and to determine if the use of a commercial nasal bridle decreases accidental tube dislodgements. Methods: Medical records of pediatric patients with NGT insertion for dsLTP between Jan 1, 2012 and June 15, 2018 were reviewed for nasal bridle use, demographics, feeding tube and bridle complications, x-rays to check NGT placement, length of stay (LOS), length of bridle use and accidental feeding tube dislodgements. Results: A total of 67 patients (34 unbridled and 33 bridled) received an NGT after dsLTP. No differences in demographics were noted, except the bridled group was older (median age 6.5 [IQR: 3.7, 14.3] than the unbridled group (median age 3.2 [IQR: 2.2, 6.8], p = 0.05). There were 24 episodes of NGT dislodgement in 16 patients in the unbridled group and zero displacements in the bridled patients resulting in an incidence of 9.4 [95%CI: 6.0, 14.0] and 0.0 [95%CI: 0.0, 1.9] pullouts per 100 days for unbridled versus bridled patients, respectively. Those with displacement had significantly more x-rays to check placement (p = 0.0004) and LOS was longer (p = 0.06) with a mean (SD) of 10.9 (7.0) vs. no displacement 7.0 (3.6) days. Of those bridled, 67% were discharged with a bridle and 86% returned with the NGT and bridle in place (mean bridle placement of *** ± days) at the time of stent removal. No feeding tube or bridle complications were reported for either group. Conclusion: The commercial nasal bridle significantly reduced NGT displacements without complication in the examined pediatric sample s/p dsLTP. Bridle use was associated with decreased radiology exposure and LOS and was successfully used in the outpatient setting.